Evaluation of thrips (Thysanoptera: Tripidae) monitoring with commercial acrylic traps of different colors in a commercial chrysanthemun crop - MEDINA, GUILLERMO; ESCOBAR, JOHNNY H.; ACOSTA, ALFREDO (Revista Colombiana de Entomología, 1994)
A trial was carried out in a commercial chrysanthemum crop in Madrid (Cund.), to monitor a thrip population, by using sticky acrylic boards of different colors, white, yellow and three blue tonalities. The traps area was 96.774 cm2 and they were divided into 15 squares of 6.4516 cm2 each one (3 columns and 5 rows) and they were distributed within the greenhouse in the chrysanthemum crop, cultivar Polaris. The blue tonality with a wavelength of 440 nm and 53.52% reflectance was the most effective for capturing adult thrips and it was the least affected by environmental factors. The trap side located outwards recorded the largest capture, suggesting that thrips migration occurs mainly from the outside towards the in, side of the greenhouses. The light blue tonalities excites a greater thrip’s attraction than the dark ones. Yellow color attracts better other insects like leafminers and whitefly adults. Finally, analysis of the results showed that it is sufficient and representative to read just one column of the trap (5 squares), which facilitates and reduces the monitoring costs.